Improvement of reading comprehension and rhetoric speaking skills of elementary school students through mind-mapping strategies - Ari Kusmiatun (JOURNAL OF EDUCATION, 2008)
Abstract:  This action research study aimed at improving students ~skills in reading comprehension and rhetoric speaking through mind-mapping strategies. The study was conducted at SD Muhammadiyah Purwodiningratan2 Yogyakarta. The subjects were 29 students in the VIa class consisting of 17 boys and 12 girls. Data were gathered by the use of intensive observations,questionnaires, and interviews. The study was conducted in two cycles. The results showed that the application of mind-mapping strategies in Bahasa Indonesia teaching-learning process, could improve students' speaking and reading skills".  Students were able to comprehend the passage  better and perform rhetorical speaking morefluently. Similarly, students' speaking skills in both language and non-language aspects improved significantly.Keywords: reading   comprehension,   rhetoric   speaking,   mind   mapping strategy,  silent  reading,  oral  reading,  communicative  language  skills,. motivation, reading texts